(untitled) (International Journal of Physiotherapy, 2019)
Background: Neuropathic pain is a compound, persistent pain condition that results from illness or damage to the peripheral nervous system, central nervous system, or both. The nerve might get compressed due to various factors but one of the causes is an increase in oncotic pressure of interstitial fluid which may lead to neuropraxia. So, this may lead to symptoms of peripheral neuropathy. The objectives of the study were to determine the prevalence of peripheral neuropathy in chronic musculoskeletal oedematous conditions and to study the association of peripheral neuropathy in chronic musculoskeletal oedematous conditions with demographic variables. Methods: A total of 52 subjects were assessed and all were included in the study based on inclusion criteria. Peripheral neuropathy was diagnosed using Modified Total Neuropathy Score (mTNS) and pain assessment using Visual Analogue Scale (VAS), oedema assessment and also musculoskeletal assessment was done for assessing the severity of peripheral neuropathy. Results: Statistical results suggests that the prevalence of peripheral neuropathy in chronic musculoskeletal oedematous conditions having moderate neuropathy symptoms is 0.8445, the prevalence of minor neuropathy symptoms is <0.0001 and moderately severe symptoms is <0.0001. As the maximum population has moderate neuropathy symptoms, the prevalence of peripheral neuropathy in chronic musculoskeletal oedematous conditions is 0.8445. Conclusion: Among the fifty-two subjects having oedema, twenty-seven subjects had moderate neuropathy symptoms, fourteen subjects had minor neuropathy symptoms and eleven subjects had moderately severe symptoms. Thus, it clarifies that subjects having oedema are likely to get neuropathic symptoms at a later stage.